Financial Technology (Fintech) and Cybersecurity: A Systematic Literature Review. - Ahmed Abdulrhman B. Alodhiani (المجلة العربية للعلوم الإنسانية والاجتماعية, 2023)
This research aims to identify the threats posed by cybercrime to the fintech sector, as well as the preventative measures taken by the industry in the form of cybersecurity. This study employs a systematic literature review approach to analyzing previously published publications on cybercrime and cybersecurity in the financial technology industry. The survey found that cybercrime issues in the fintech industry include lax cybercrime rules, theft of data and information, and infringement of intellectual property. Proactive measures strengthened legislation, and establishing a trustworthy cybersecurity framework or system may all be used to combat cybercrime in the fintech industry. This study’s findings may serve as a resource for academics, practitioners, regulators, and fintech players interested in learning more about the evolution of cybercrime and cybersecurity in the financial technology sector. While this study does an excellent job of summarizing and expanding upon the research findings in each chosen article, it needs to analyze the connections between the pieces. Broadening the scope of the article under evaluation, using other literature review techniques, or doing more empirical research are all viable options for recommending additional studies to corroborate the findings of the current one.